Effectiveness of Noise Barriers Based on Waste Materials in Case Study of Residential Noise Due to Double-Track Railways - Febrianti, Denisa Eka; Agus Salim, Alfi Tranggono; Rezika, Wida Yuliar; Annas, Muhamad Azwar; Suyatno, Suyatno (Journal of Physics and Its Applications, 2023)
The noise pollution in residential areas adjacent to double-track railways can significantly disturb the comfort and well-being of residents. The noise originates from passing trains on these double-track railways. The research problem aims to compare the noise levels in the residential area with the standard noise threshold and evaluate the effectiveness of a noise barriers based on waste material called sustainable noise barrier. The effectiveness of reducing noise levels for communities residing near the dual railway lines. The sustainable noise barrier is constructed using waste cardboard and sawdust as sound absorbers for reducing noise from passing trains. The objective of the research is to analyze the noise levels in the residential areas near the dual railway lines, referring to the noise threshold value specified in Kep.MenLH No.48 of 1996, which is 55 dBA. Additionally, the research aims to assess the effectiveness of the sustainable noise barrier in mitigating noise pollution in these residential areas. The research employs a quantitative experimental method, following the SNI 8427 of 2017 standard for measuring residential noise pollution and determining the sustainable noise barrier's effectiveness using Insertion Loss (IL) and Sound Transmission Loss (STL) measurements in both laboratory-scale and existing conditions (alongside the double-track railways). The research findings indicate that the noise levels in residential areas adjacent to dual railway lines exceed the threshold value, reaching 78.08 dBA. However, the sustainable noise barrier proves to be effective in reducing noise pollution by 27 dB at a frequency of 1,000 Hz in the residential areas neighboring the double-track railways. This research suggests that limiting noise disturbances in residental areas bordering railway lines is one solution with noise barriers.